Secukinumab 150/300 mg Provides Sustained Improvements in the Signs and Symptoms of Active Ankylosing Spondylitis: 3-Year Results from the Phase 3 MEASURE 3 Study - Pavelka, Karel; Kivitz, Alan J; Dokoupilova, Eva; Blanco, Ricardo; Maradiaga, Marco; Tahir, Hasan; Wang, Yi; Porter, Brian O; Stefanska, Anna; Richards, Hanno B; Rohrer, Susanne; MEASURE 3 study group (ACR open rheumatology, 2020)
OBJECTIVE: Secukinumab 150 mg has demonstrated significant improvement in signs and symptoms of ankylosing spondylitis (AS), with response rates sustained for up to 5 years. Here, we report end-of-study 3-year efficacy and safety results of secukinumab 150 and 300 mg from the MEASURE 3 study. METHODS: A total of 226 patients was randomized to intravenous secukinumab 10 mg/kg (baseline, weeks 2 and 4) followed by subcutaneous (s.c.) secukinumab 300/150 mg every 4 weeks or a matched placebo. At week 16, placebo patients were re-randomized to s.c. secukinumab 300/150 mg. Analysis at week 156 included patients initially randomized to secukinumab and those who switched from placebo to secukinumab at week 16 (any secukinumab 300/150 mg). Outcome measures at week 156 included Assessment of Spondyloarthritis International Society (ASAS) 20/40, Bath Ankylosing Spondylitis Disease Activity Index, ASAS partial remission (PR), ASAS 5/6, and Ankylosing Spondylitis Disease Activity Score-C-reactive protein inactive disease. RESULTS: The retention rates from weeks 16 to 156 were 80.5% and 80.9% in secukinumab 300 and 150 mg, respectively. ASAS 20/40 response rates at week 156 were 75.0%/56.5% and 68.2%/47.7% for secukinumab 300 and 150 mg, respectively. At week 156, response rates on more stringent clinical end points (eg, ASAS 40, ASAS-PR) were higher with the 300-mg dose, particularly in tumor necrosis factor (TNF)-inadequate responder (IR) patients. No new safety findings were observed. CONCLUSION: Secukinumab (300 and 150 mg) provided sustained improvements through 3 years in the signs and symptoms of active AS. Improvements with secukinumab 300 mg were numerically higher compared with the 150-mg dose for some higher hurdle end points and in TNF-IR patients. The safety profile of secukinumab was consistent with previous reports.